Suggestions on cyber security talents cultivation - Hui LI; Ning ZHANG (网络与信息安全学报)
Cyber security has been approved to be the first level discipline by Academic Degrees Committee of the State Council.It is important to figure out the curriculum of this new discipline and make it clear what is the differ-ence between this new discipline and existed ones.The relationship between cyber security discipline and other dis-ciplines such as information and communication engineering,computer sciences and technology,etc was analyzed.The cyber security was divided into 5 research areas,including fundamental theory,physical security,network secu-rity,system security,data and information security.Based on a given knowledge framework,the cultivation standard for master and Ph.D.students,as well as a reference curriculum of cyber security discipline was proposed.Finally,some suggestions were given for training talents of cyber security.